Gorontalo Province Tourism: Leading Sector In The Middle Of Weakness And Challenge - Herwin Mopangga; Fitriaty Puhi (Jambura Equilibrium Journal, 2019)
Tourism shows a significant contribution to foreign exchange and regional income in Indonesia. Defined as a priority and leading sector in the RPJMD, tourism development in the Regencies and the Province of Gorontalo must measure the results, benefits and impacts for all stakeholders. Contribution to regional income (PAD) and the composition of internal and external factors in each of the leading destinations is needed for the purpose of determining the strategy and policy of sustainable tourism development. The study concluded that tourism sector was relatively small in its contribution to each PAD total by Regencies in Gorontalo Province. The low of PADsp is relevant to the low occupancy rate (TPK) of the hotel and the length of stay (LoS). The lack of retribution income from recreation and sports spot is relevant to the lack of activities to support the attractiveness such as art and cultural attractions and local products that can be souvenirs for tourists. Infrastructure facilities at leading tourism objects are relatively incomplete or do not meet tourism standards. The low of PAD, TPK & LoS can also explain that the increase in tourists to Gorontalo is only a transit to the other tourist objects outside of Gorontalo Province.